ANALYSIS OF SOCIAL MEDIA OPPORTUNITIES AS MARKETING MEDIA FOR ASSALAAM ISLAMIC MODERN BOARDING SCHOOL SURAKARTA TOWARDS THE INTERNATIONAL MARKET - Pertapa Sari (Pondok Pesantren Modern Islam Assalaam, 2023)
This study aims to determine the effectiveness of the marketing media for the modern Islamic boarding school Assalaam Surakarta towards the international market. The method used in this study is a qualitative method using a descriptive approach in the form of a literature study conducted by interviews and documentation, coupled with observations made by researchers. The data is taken from the database entered by the PR and IT team of PPMI Assalaam. From this research, it can be concluded that the social media used by PPMI Assalaam has a high chance to be used as a means of promoting the agency’s marketing in the international market